Implementasi Anggaran Dana Desa Kasembon Yang Ditinjau Dari Pengalokasian Dan Pengembangan - Ivan Adi Priyono; Jeni Susyanti; Budi Wahono (E-JRM : Elektronik Jurnal Riset Manajemen, 2022)
AbstractFinancial management is very important in terms of business, budget or other management such as Village Fund Budget (ADD). The village has the right to regulate its territory which includes public policy, village fund finance, implementation of development and development. The Village Fund Budget (ADD) itself is a fund derived from the District or City BUDGET obtained from central and regional finance allocated from the government then transferred to the region and intended for the area itself. The author will make observations to collect general data as research material whether financial management in Kasembon Subdistrict has been running and carried out in accordance with theory, and evaluate the performance of staff members in Kasembon Subdistrict. This study the author using a qualitative method. Village funds either in terms of management or in terms of taking policies need to be done. Community involvement in the village fund always prioritizes deliberation and mufakad both fellow communities themselves and to community leaders of Kasembon Subdistrict. Another impact of the village fund on the people of Kasembon Subdistrict, namely the development of infrastructure and non-infrastructure, the village is more advanced with development and it is expected that the village can grow independently. Factors that affect the effectiveness of village fund management is human resources, data collected by author during research process identified that there is a form of realization in the form of physical development that can be enjoyed by the community, especially Kasembon Subdistrict since the village fund. The effectiveness of management is also felt by the community, because the development carried out is a community need to support the empowerment of human resources in the future, especially in Kasembon District. Furthermore, this deliberation activity resulted in a village fund management plan related to the financial management of the village itself as well as the development plan to be carried out. The next step then the village device makes RKP Desa, then continued by making the village fund. Village funds with covering the receipt and expenditure of funds. The Kasembon District Government disbursed funds, then after that it was spent in accordance with what was estimated in the Village Fund and carried out programs that had been jointly prepared at village deliberations. Keywords : Implementation, Village Fund, Allocating, Development